Literature Review: Efektivitas Strategi Pembelajaran Computational Thinking pada Pelajaran Sosiologi bagi Murid Slow Learner - Andhy Surya Hapsara (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2026)
This literature review analyzes the effectiveness of computational thinking (CT) learning strategies in sociology education for slow learner students. Using a systematic approach with an adapted PRISMA framework, literature searches were conducted on Scopus, Web of Science, ERIC, Google Scholar, and Portal Garuda databases for publications from 2018 to 2025. From 247 initial articles, 10 studies met the inclusion criteria and were analyzed using thematic narrative synthesis. The findings reveal that although empirical evidence in STEM and literacy domains consistently demonstrates the effectiveness of CT in improving problem-solving skills of slow learner students (score improvements ranging from 50% to 300%), no single study was found that specifically examines CT in sociology education for this population. Critical analysis uncovered four main research gaps: (1) the absence of empirical studies on CT-sociology-slow learner; (2) unknown causal mechanisms of CT effectiveness in social reasoning; (3) unidentified effectiveness moderators in the sociology context; (4) untested transfer of CT from quantitative domains to sociological reasoning. A conceptual model integrating Cognitive Load Theory, Piaget's theory, Self-Determination Theory, and Bandura's social learning theory is proposed as a framework for future research. This review recommends the development of CT-Sociology assessment instruments, cross-modal experimental studies, and longitudinal research to fill the existing gaps.